Trends in Determinants of Birth Interval based on Data from the Indonesian Demographic Health Survey in 2007, 2012, and 2017 (Althea Medical Journal, 2022)
Background: Fertility is the main component of population dynamics that determines the population structure of a country. One method to measure fertility is to analyze the birth interval. This study aimed to identify determinants of birth interval based on the Indonesian Demographic and Health Survey (IDHS) data in 2007, 2012, and 2017.Methods: This study design was descriptive using IDHS data from 2007, 2012, and 2017 with a cross-sectional study design. Samples were mothers who gave birth to their last living child in the last five years.Results: In the IDHS 2007, the birth interval at risk (
Keywords: Birth interval; female reproduction; health of mother and child